Algorithm-program visualization model : An intergrated software visualzation to support novices' programming comprehension - Affandy (2015)
Computer programming is the essential foundation for the other basic skills in Information Technology knowledge areas. Success in this field requires complex knowledge and skill. Mostly, conventional programming courses have been delivered based on the programming textbooks with professional developer tools which focus on the syntax or semantic through the coding task. The role of Software Visualization (SV) has been involved to overcome the complexity and problems in the learning programming. It represents the abstractness of the program in graphical views or illustrations of its entities. Nevertheless, the outcome of the learning still remains poor. Through multi-methodological approach, this research aimed to improve the effectiveness of the visualization as the program comprehension tool. It is found that the interrelated tasks in the programming process, with its various abstractions, and timing in delivering the feedback, need to be addressed with the equal attention in learning to program. Taking into account from those main issues, this study introduces the new model of integrated algorithm-program visualization (ALPROV) for developing program comprehension tool. This model is then to be used in the prototype tool development that is called 3De-ALPROV (Design Development Debug – Algorithm Program Visualization). The efficacy evaluation of the prototype is based on pre- and post- test of the students’ programming performance. The programming performances from the treatment and control group are compared to analyze the effect of using the proposed tool in learning programming. Respondents are first-year bachelor students who lack of programming knowledge and experience.Analysis proved that using the program comprehension tool, which has been developed using integrated ALPROV model significantly improved the treatment group’s programming performance. Conducting other experiments as the extended study, such as seek for a larger group of respondents, conduct the experiments throughout the necessary period, and use various methods for programming assessment and analysis may improve the findings of this research.